2020
DOI: 10.1109/jmmct.2020.2982766
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study and Numerical Investigation of an Electrostatic Unit for the Removal of Fluoride From Thermal Water of Ethiopian Rift Valley

Abstract: This article deals with the numerical modeling of the multiphysics investigation of an electric-field-based device for the defluoridation of Ethiopian water to mitigate fluorosis while satisfying the World Health Organization quality requirement for potable water. A tubular reactor with metallic parallel plates, connected to a static voltage source, exerts an electric force on the ion in solution, attracting it to the electrodes. Meanwhile, the ion is drifted by the laminar water flow which, in turn, allows us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The ideal outcome would be to have a technology that allows the use of the resource, of any origin, ensuring the correct balance of the substances contained through the self-regulation of the device. This technology is under study [129], although still in the preliminary phase, but this allows us to be moderately optimistic about a solution in the near future.…”
mentioning
confidence: 99%
“…The ideal outcome would be to have a technology that allows the use of the resource, of any origin, ensuring the correct balance of the substances contained through the self-regulation of the device. This technology is under study [129], although still in the preliminary phase, but this allows us to be moderately optimistic about a solution in the near future.…”
mentioning
confidence: 99%
“…In terms of electromagnetic flux, the current density associated with the membrane potential generated by bacteria is typically in the order of . This relatively high, but extraordinarily localized in space (membrane of bacteria) and time (10–100 ms), density current could generate two-way coupling phenomena between the electromagnetic signal and fluid flow as analyzed in [ 68 ]; in their work, the fluid studied is dilute in electrical charges, and consequently the electromagnetic forces are finally neglected. Similarly in this problem, the impact of the electromagnetic signal on the fluid phase, which is also electrically dilute, in addition to be activated sporadically and for a small period of time, exponentially decays as (diffusion term in Poisson-Nernst-Planck-Stokes equation in spherical coordinates [ 69 ]).…”
Section: Discussion On Membrane Potential Detectionmentioning
confidence: 99%
“…In fact, the viscosity, which increases in high-concentration solutions, dominates the concentration dependence of D for some systems. Nevertheless, PB theory has many shortcomings because it neglects ion-ion interactions and steric effects and it is proposed that the electrolyte dynamics are better described by a modified form of the PNP equations [12,23]. From a macroscopic point of view, studied under the Poisson-Boltzmann (PB) theory, it has been shown that the response of an electrolyte to an applied voltage leads to sharp ion concentration near a surface [21,22].…”
Section: Shear Viscosity Calculationsmentioning
confidence: 99%
“…In fact, the viscosity, which increases in high-concentration solutions, dominates the concentration dependence of D for some systems. Nevertheless, PB theory has many shortcomings because it neglects ion-ion interactions and steric effects and it is proposed that the electrolyte dynamics are better described by a modified form of the PNP equations [12,23].…”
Section: Shear Viscosity Calculationsmentioning
confidence: 99%
See 1 more Smart Citation